2004
DOI: 10.1023/b:neab.0000018751.74369.89
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Tremor in Normal Subjects and in the Diagnosis and Treatment of Parkinsonism

Abstract: Tensotremorography was used to record voluntary forces and to study the characteristics of the involuntary and voluntary components of isometrically recorded hand strength. The frequency ranges for changes in the spectral density of oscillations recorded here supported the existence of two suprasegmental systems associated with voluntary control and continuous regulation of force maintaining or holding a posture. Cross-correlation analysis of hand force maintained in conditions of visual feedback in normal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Thus, the prototype’s tests showed that tensometric tremorography as a part of isometric measurements can be used in medical diagnostics systems. 35 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the prototype’s tests showed that tensometric tremorography as a part of isometric measurements can be used in medical diagnostics systems. 35 …”
Section: Resultsmentioning
confidence: 99%
“…After the AKM has performed, the centers coordinates, some adjustable parameters should be presented to the Gaussian Mixture Model Method (GMM) [2]. Gaussian Mixture Model [3] is a type of density model, comprising a number of functions (components), namely Gaussians. These component functions are combined to provide a density function.…”
Section: The Adaptive Binary Classifier Methods Descriptionmentioning
confidence: 99%
“…The received signaltensotremorogram (TTG) is being converted into the digital form and saved for the further processing. Earlier we showed, that in cases of the motor control system dysfunction, the characteristics of TTGs from patients differ from ones from healthy subjects [2][3][4]. It is necessary to note, that the method described in [1], differs principally from the frequently used methods of tremor registration as fingers ballistics by the accelerometers.…”
Section: Introductionmentioning
confidence: 99%